Application of search criteria and text selection for the elaboration of academic works in university students: a case study - Azcona Avalos, Guisella Ivonne (2021)
The present investigation shows the difficulties that students present for the application of search criteria and selection of texts for the preparation of academic works in the first year of university. Based on this, an improvement proposal was presented that consisted of three didactic workshops in three groups of the face-to-face modality and in three groups of the blended modality of the Technological University of Peru, execut-ed in the second semester of 2019. Likewise, we worked according to the interpretive paradigm, qualitative approach, descriptive design and inductive method. It is concluded that there were diverse effects both in the face-to-face and blended modality, in the permanence of studies, in the assimilation of learning and in the uses of technological information resources for academic research.